Oxford Handbook of Neurology - Manji, H. Hadi (University press, 2014)
The Oxford Handbook of Neurology is a practical and concise, quick reference guide for use on the ward and in clinical settings. It covers the entire breadth of neurology with sections on neuroanatomy, neurosurgery, neuroradiology and neurophysiology. It provides information on neurological assessment, neurological presentations and disorders.